TIR1/AFB proteins: Active players in abiotic and biotic stress signaling - Du, Wenchao; Lu, Yang; Li, Qiang; Luo, Shuangxia; Shen, Shuxing; Li, Na; Chen, Xueping (Frontiers in Plant Science, 2022)
The TIR1/AFB family of proteins is a group of functionally diverse auxin receptors that are only found in plants. TIR1/AFB family members are characterized by a conserved N-terminal F-box domain followed by 18 leucine-rich repeats. In the past few decades, extensive research has been conducted on the role of these proteins in regulating plant development, metabolism, and responses to abiotic and biotic stress. In this review, we focus on TIR1/AFB proteins that play crucial roles in plant responses to diverse abiotic and biotic stress. We highlight studies that have shed light on the mechanisms by which TIR1/AFB proteins are regulated at the transcriptional, post-transcriptional, and protein levels, as well as the downstream in abiotic or biotic stress pathways regulated by the TIR1/AFB family.